2013
DOI: 10.1137/120874643
|View full text |Cite
|
Sign up to set email alerts
|

Preasymptotic Error Analysis of CIP-FEM and FEM for Helmholtz Equation with High Wave Number. Part II: $hp$ Version

Abstract: In this paper, which is the second in a series of two, the preasymptotic error analysis of the continuous interior penalty finite element method (CIP-FEM) and the FEM for the Helmholtz equation in two and three dimensions is continued. While Part I contained results on the linear CIP-FEM and FEM, the present part deals with approximation spaces of order p ≥ 1. By using a modified duality argument, preasymptotic error estimates are derived for both methods under the condition of kh, where k is the wave number, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 52 publications
(173 reference statements)
2
116
0
Order By: Relevance
“…For example, with an appropriate choice of coefficients, low-order compact finite-difference discretizations can effectively reduce the dispersion error [35,58,80]. Other instances of such approaches are the generalized finite element method (GFEM) [4] and continuous interior penalty finite element method (CIP-FEM) [107,111], the interpolated optimized finite-difference method (IOFD) [93,94], Galerkin methods with hp refinement [70,72,73], among many others. These methods successfully reduce the pollution error; however, they require either a more restrictive condition on the mesh size or the degree of the polynomial approximation to be ω dependent, resulting on a large increase in the size and interconnectivity of the associated linear systems as the frequency increases.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, with an appropriate choice of coefficients, low-order compact finite-difference discretizations can effectively reduce the dispersion error [35,58,80]. Other instances of such approaches are the generalized finite element method (GFEM) [4] and continuous interior penalty finite element method (CIP-FEM) [107,111], the interpolated optimized finite-difference method (IOFD) [93,94], Galerkin methods with hp refinement [70,72,73], among many others. These methods successfully reduce the pollution error; however, they require either a more restrictive condition on the mesh size or the degree of the polynomial approximation to be ω dependent, resulting on a large increase in the size and interconnectivity of the associated linear systems as the frequency increases.…”
Section: Related Workmentioning
confidence: 99%
“…2 Adaptive methods, on the other hand, aim to leverage à priori knowledge of the solution of the Helmholtz equation, such as its known oscillatory behavior. In practice, adaptive methods have mostly focused on adaptivity to the medium, such as polynomial Galerkin methods with hp refinement [3,70,73,96,107,111], specially optimized finite differences [23,45,92,93,102] and finite elements [4,99], enriched finite elements [30][31][32][33], plane wave methods [5,21,42,43,46,69,74], generalized plane wave methods [54,55], locally corrected finite elements [17,38,82], and discretizations with specially chosen basis functions [7,8,76], among many others. They have been especially successful on reducing the pollution effect by accurately capturing the dispersion relation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the results on linear CIP-FEM in two and three dimensions (see [31,33,17]), the above estimate (1.2) for the case of real penalty parameters is unique in two ways. First, the mesh condition kh 1 is weaker than the requirement that k 3 h 2 is bounded, the latter being the condition required in general dimensions.…”
Section: Introductionmentioning
confidence: 64%
“…Since the phase difference of the CIP-FE solution can be reduced by tuning the penalty parameter, so can its pollution error. Recently, the authors [31,33] showed for the CIP-FEM and FEM in higher dimensions that the pollution errors in H 1 -norm are of the same order as the phase difference of the FE solution. In the higher dimensional case, although the phase difference of the CIP-FE solution can still be reduced by tuning the penalty parameter, no theoretical result says that the reduced phase difference can also control the pollution error.…”
Section: Stability and Preasymptotic Error Estimates For The Cip-femmentioning
confidence: 99%
See 1 more Smart Citation